Mortality in Bacteremia Patients with Bacteria Unidentified by Verigene® - Kue, Kenneth; Kale-Pradhan, Pramodini; Giuliano, Christopher; Marshall, MaryBeth; Johnson, Leonard B. (Anti-Infective Agents, 2026)
IntroductionVerigene® is a molecular rapid diagnostic test (mRDT) that identifies certain organisms and resistance markers within 2.5 hours of blood culture positivity and can potentially aid in reducing the time to appropriate antibiotic therapy, thus improving patient outcomes. However, Verigene® is not calibrated to detect all organisms and resistance markers.ObjectiveTo assess outcomes of patients with bacteremia in whom Verigene® identified organisms (BOI) and compare them to patients with bacteremia in whom Verigene® did not identify an organism (BON).MethodsSingle-center, retrospective cohort study evaluating inpatients admitted between May 2020 to June 2021. The primary outcome was to compare the inpatient mortality rates of patients with BOI with patients with BON. Secondary outcomes include 30-day readmission rate, reason for readmission, appropriateness of antibiotic therapy at time of final blood culture result, time to appropriate antibiotic therapy, and length of stay (LOS).Results and Discussion100 and 79 patients were included in the BOI and BON groups, respectively. Mortality was significantly higher in the BON group compared to the BOI group (31.6% vs 14%, respectively, p < 0.01). A significantly shorter time to appropriate antibiotics was observed in the BOI group compared to the BON group (0.6 + 1.1 days vs 0.9 + 1.1 days, respectively, p= 0.04). This observation was larger in the critically ill population.ConclusionIn conclusion, our study found a significant difference in mortality and time to appropriate antibiotics between groups when Verigene® could and could not identify the organism.
Keywords: Rapid diagnostic test